2007
DOI: 10.1093/chromsci/45.8.544
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Pharmacokinetics of 6,7-Dimethoxycoumarin in Rat Plasma after Intragastric Administration of Different Decoctions of Yinchenhao Tang

Abstract: A simple and sensitive reversed-phase high-performance liquid chromatography method with UV detection is developed and validated for the determination of 6,7-dimethoxycoumarin in rat plasma and comparative analysis of its pharmacokinetics after intragastric administration of 6,7-dimethoxycoumarin and three different decoctions of yinchenhao tang. The plasma samples are deproteinated with acetonitrile. The components are separated on a Kromasil C18 column (250 x 4.6 mm, 5 microm,) with methanol-1% acetic acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…After oral administration of DFD, the AUC 0– t , AUC 0–∞ and C max of BHA, BMA, BAC and HA decreased remarkably ( p < 0.05) compared with those of the FZ extract group. Although the results of absorption enhancement after combination owing to the competitive inhibition between components in herbs on P‐glycoprotein (P‐gp) or the inhibition against metabolism of CYP3A have been documented in many reports regarding to the comparative pharmacokinetics after combination (Wu et al ., 2009; Xu et al ., ; Xiao et al ., ; Yu et al ., ; Yan et al ., ; Tong et al ., 2010), quite a few studies have reported that absorption of effective components decreased after combination, especially for the combination regarding toxic herbs (Yan et al ., ; Wang et al ., ), which is in agreement with the results of our study. In addition, the T 1/2 values of BHA, BMA and BAC in DFD group were significantly delayed compared with those of the FZ extract group ( p < 0.05 for BHA, BMA; p < 0.01 for BAC), indicating that DFD could postpone the elimination of BHA, BMA and BAC in rats.…”
Section: Resultsmentioning
confidence: 99%
“…After oral administration of DFD, the AUC 0– t , AUC 0–∞ and C max of BHA, BMA, BAC and HA decreased remarkably ( p < 0.05) compared with those of the FZ extract group. Although the results of absorption enhancement after combination owing to the competitive inhibition between components in herbs on P‐glycoprotein (P‐gp) or the inhibition against metabolism of CYP3A have been documented in many reports regarding to the comparative pharmacokinetics after combination (Wu et al ., 2009; Xu et al ., ; Xiao et al ., ; Yu et al ., ; Yan et al ., ; Tong et al ., 2010), quite a few studies have reported that absorption of effective components decreased after combination, especially for the combination regarding toxic herbs (Yan et al ., ; Wang et al ., ), which is in agreement with the results of our study. In addition, the T 1/2 values of BHA, BMA and BAC in DFD group were significantly delayed compared with those of the FZ extract group ( p < 0.05 for BHA, BMA; p < 0.01 for BAC), indicating that DFD could postpone the elimination of BHA, BMA and BAC in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Both CDCA and SC were assayed at 10 µM, a concentration that is widely used under laboratory conditions (Huang et al ., 2004; Kaimal et al ., 2009). The concentration of total bile acids in the blood in cholestasis ranges from 10 to 30 µM (Brites et al ., 1998), and it is estimated that SC reaches 10–20 µM in the liver after oral administration; this is based on a pharmacokinetic study in rats (Yu et al ., 2007). As expected, CDCA efficaciously increased BSEP but had little effect on CYP2B6 or UGT1A1 (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several publications are available on the pharmacokinetic properties of the above 1-3 active components in YCHT in healthy rats [ 2 , 9 , 23 25 ]. However, researchers have presented that chemicals' pharmacokinetic profile may be influenced by liver disease, such as liver fibrosis [ 26 , 27 ] and nonalcoholic fatty liver disease [ 28 ].…”
Section: Introductionmentioning
confidence: 99%